STEAM GASIFICATION OF PALM SHELL TO PRODUCE HIGH HYDROGEN CONCENTRATION OF SYTHESIS GAS - Raihan Sirhindi, Muhammad
With the fourth largest population in the world, the energy issue in Indonesia is a rather crucial topic. Energy in Indonesia can be fulfilled using biomass, considering that Indonesia is an agrarian nation with an abundance of biomass waste. One of the methods that can be used to utilize biomass as an energy source is the gasificaion process. Gasification uses biomass as feedstock and produces gases rich in H2 and CO. The gasification process is done in a tubular downdraft reactor and uses steam as the gasification medium. The effects of char quantity and steam to carbon ratio will be analyzed from the result of the hydrogen concentration in the producer gas and the heating value (LHV) of the producer gas. The gasification process is done under atmospheric conditions at 700°C with the steam to carbon ratio varied between 1.3 and 3. The bed height is varied at 8, 13, and 17 cm. To model and predict the composition of the producer gas, thermodynamic analysis is used in the form of the equilibrium of the reations involved in the gasification process. From the steam to carbon ratio variation, the highest concentration of hydrogen in the producer gas is obtained when the steam to carbon ratio is 3, with a value of 53.90%. The highest LHV is also obtained when the steam to carbon ratio is 3, with a value of 158 kJ/mol. When the bed height is varied, the highest concentration of hydrogen in the producer gas is obtained when the bed height is 17 cm, with a value of 59.01%. The highest LHV is also obtained when the bed height is 17 cm, with a value of 185.4 kJ/mol. From both of these variations, it can be concluded that an increase in steam to carbon ratio and bed height will increase the hydrogen content in the producer gas.